Mendorong Kinerja Tinggi: Sinergi Strategi Disiplin Karyawan dan Kompensasi - Inna Nisawati Mardiani; Rosyid Anafi (CV. ITTC INDONESIA, 2023)
In the current era of globalization, companies are required to be more competitive. Companies must have advantages and competitiveness, so that they can survive among other companies. The company's success is strongly influenced by its employees, namely human resources (HR). The formulation of the problem in this study is to determine and analyze the effect of work discipline on employee performance, to determine and analyze employee compensation on employee performance, and to determine and analyze the effect of work discipline and employee compensation on the performance of employees in the production department of the cutting section of PT. Maxxis International Indonesia. Employee performance is an extension of the meeting of individuals and expectations about what individuals should do in relation to a role. Work discipline is a tool used by leaders to communicate with employees so that they are willing to change behavior to follow company regulations. Compensation is intended as a reward for the company for the sacrifice of time, energy and thoughts that have been given by employees. The results of the R2 test show the figure of 53.3%, while the remaining 46.7% of employee performance is influenced by other variables not examined by researchers. Work discipline (X1) partially affects employee performance (Y) with a significance level of 0.000 <0.05 and is declared accepted. Compensation (X2) partially affects employee performance (Y) with a significance level of 0.000 <0.05 and is declared accepted. Career development (X3) partially affects employee performance (Y) with a significance level of 0.000 <0.05 and is declared accepted. Simultaneously the variables of work discipline (X1), employee compensation (X2), career development (X3) have an effect on employee performance variables with a significance value of 0.000 or less than 0.05.